Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/jz500556n
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Aqueous Microdroplet

Abstract: Directional and controllable transportation of microdroplets is critical for emerging micro- and nanotechnology, in which the conventional mechanical energy generation is not applicable. This Letter shows that an aqueous microdroplet can be charged for controlled motion in electrostatic potential, which was created by differentiating pH, between two oil/water interfaces. The directional motion of the droplet, <100 μm in diameter, was obtained with a constant velocity of ∼1 mm/s. The force analysis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Herein, we summarised severals trategies to realise mobilitybased dynamic behaviour in various microcompartments, including sliding on as urfacei nr esponse to an adhesion gradient, horizontal movement through al iquid driven by external chemicalg radient or the internal Marangoni effect, as well as buoyancy-powered verticalm ovement through as olution.I ti s anticipated that our discussion will attracta ttention from different research communities for the design of variouss mart dynamic behaviours in microcompartments. In particular,g iven that mobility is one of the fundamental properties of life, the furtherd esign of microcompartments towards protocell modelsw ith advanced dynamic behaviour still requires much attentiont ot he following aspects:1 )currently mostm otion is still controlled by "fuel", although inspired by the sustained flux of energy and matter exchange for maintaining basic life in natural cells, but the integration and boosting of metabolism and self-organisation to create self-sustainable mobility in the protocell model is stillac hallenge;2 )only af ew constructed microcompartments can autonomously control their movement on/off or backwards/forwards ; [34,43,48,59] therefore, the precise spatiotemporal control of autonomous mobility,i ncluding movement status, direction,s peed and time in the presence of non-invasive factors, is another challenging topic;a nd 3) in comparison with that of individual mobility,c ollective motility behaviour within protocell models is still rare, and similar to quorum sensingi nl iving organisms;t he development of collective motility behaviour will enhancet he properties of the designed modelsa nd contribute to understanding of the complex network interactions within protocell communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we summarised severals trategies to realise mobilitybased dynamic behaviour in various microcompartments, including sliding on as urfacei nr esponse to an adhesion gradient, horizontal movement through al iquid driven by external chemicalg radient or the internal Marangoni effect, as well as buoyancy-powered verticalm ovement through as olution.I ti s anticipated that our discussion will attracta ttention from different research communities for the design of variouss mart dynamic behaviours in microcompartments. In particular,g iven that mobility is one of the fundamental properties of life, the furtherd esign of microcompartments towards protocell modelsw ith advanced dynamic behaviour still requires much attentiont ot he following aspects:1 )currently mostm otion is still controlled by "fuel", although inspired by the sustained flux of energy and matter exchange for maintaining basic life in natural cells, but the integration and boosting of metabolism and self-organisation to create self-sustainable mobility in the protocell model is stillac hallenge;2 )only af ew constructed microcompartments can autonomously control their movement on/off or backwards/forwards ; [34,43,48,59] therefore, the precise spatiotemporal control of autonomous mobility,i ncluding movement status, direction,s peed and time in the presence of non-invasive factors, is another challenging topic;a nd 3) in comparison with that of individual mobility,c ollective motility behaviour within protocell models is still rare, and similar to quorum sensingi nl iving organisms;t he development of collective motility behaviour will enhancet he properties of the designed modelsa nd contribute to understanding of the complex network interactions within protocell communities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Phan reported the vertical movement of ar echargeable aqueous microcompartment in an electrostatic field. [59] The pH values of the top and bottom aqueous solutions were 13 and 8, respectively,r esulting in an electrostatic potentialo ft he oil medium between the two oil/water interfaces. The aqueous microcompartments werec harged by con-tact with the interface and bounced between the two oil/ water interfaces.…”
Section: External Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few works that describe vertical motion. As an example, Phan [79] has demonstrated the vertical oscillation of a water droplet between two stationary water-oil interfaces. This mechanism of oscillatory motion is not due to magnetism, but rather to the electrostatic interaction of the droplet with either interface.…”
Section: Other Types Of Droplet Movementmentioning
confidence: 99%
“…3 Numerous studies [3][4][5][6][7][8][9][10][11][12][13] have reported various modes of droplet motion between electrodes using both experimental and numerical methods. A droplet behaves as an electrical charge-carrier between a pair of electrodes in an oil medium as an insulator.…”
Section: Introductionmentioning
confidence: 99%